Safety of 1000 CT-Guided Steroid Injections with Air Used to Localize the Epidural Space - Chang, A.; Pochert, S.; Romano, C.; Brook, A.; Miller, T. (American Journal of Neuroradiology, 2011)
SUMMARY: Historically, ESIs were performed without any imaging guidance, resulting in erroneous placement in up to 30% of injections. Fluoroscopic imaging is now used to guide most procedures. Recently, several reports have described the use of CT to guide ESIs instead of fluoroscopy. CT provides the ability to use air as contrast to localize the epidural space. This retrospective review will discuss findings in 1000 CT-guided ESIs with air localization. ADRadverse drug reactionESIepidural spinal injection